Determination of Self-Development in the Vocational Educational Environment - E. F. Zeer; I. V. Meshkova (Образование и наука)
The paper explores the concept of vocational educational environment combining vocational training, professional development and professional world. The research is aimed at the self-determination analysis of an individual in the above environment. The authors observe the two existing trends of self-development analysis, corresponding with the subjective activity and culturally historical approaches. The empirical research results involve the students’ subjective individual characteristics and factors influencing the self-development strategy selection. The research findings prove the earlier hypothesis of the self- development phenomenon being determined by the two mutually conditioned factors: personal self-control ability and interrelation of the above mentioned components of the vocational educational environment. The authors make the conclusion that the self-development prospects are determined by the internal and external motivation, professional mobility and striving for success. The determination specificity of professional self- development, identified by the authors, can provide the psychological basis for future specialists training.